Gender Dysphoria in Adolescents and Preadolescents as Pedagogical Challenge - Janusz Andrzej Majcherek (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: In recent years in many countries, including Poland, there has been recorded a strong increase in the number of cases of disorders, diagnosed as gender dysphoria, among adolescents and preadolescents. This is not only a serious medical and psychotherapeutic problem, but also a pedagogical challenge. Research Aim: Research aim is to recognize and analyse needs and challenges generated for educators and preceptors by gender dysphoria that occurs in their preadolescent and adolescent pupils. Evidence-based Facts: There are not many evidence-based facts about gender dysphoria in Poland, but there are some of them in other countries, particularly in the USA. Their results can be used to anticipate the challenges faced by Polish educators. Summary: This disorder is in many cases temporary and transient, but very dangerous, because suicides, self harms and other kinds of behavioral disturbance among children and young people with this syndrome are several times more frequent than in the entire population. A main pedagogical challenge is to help them get through this growth phase and avoid discrimination by their peers. However, neither preparation for the transition nor providing assistance in bringing about the transition are pedagogical tasks.